Development of the domain name system. - Mockapetris, P. (Computer communication review.)
The Domain Name System (DNS) provides name service for the DARPA Internet. It is one of the largest name services in operation today, serves a highly diverse community of hosts, users, and networks, and uses a unique combination of hierarchies, caching, and datagram access. This paper examines the ideas behind the initial design of the DNS in 1983, discusses the evolution of these ideas into the current implementations and usages, notes conspicuous surprises, successes and shortcomings, and attempts to predict its future evolution.